ANALISIS SECOND ORDER KUALITAS DAN KEPUASAN TERHADAP LOYALITAS SAMSUNG ELEKTRONIK INDONESIA - Hary Mulyadi; Wahid Akbar Basudani; Muhammad Abdullah; Gani Wiharso (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the development of electronics in Indonesia, with the level of quality (Second Order) and satisfaction with loyalty as research variables. The research implementation is located in Jakarta-Indonesia. With Path Analysis and quantitative data taken from interviews and surveys of consumers using Samsung Electronics Indonesia products with a population of 91 people. As a measure of research data used Structural Equation Modeling (SEM) using PLS 4.0 Software for processing research data. The results of the first stage of testing the second-order Path Coefficien variable consumer satisfaction 0.053 on consumer loyalty. Variable customer satisfaction 0.571 to the quality of management. The latent variable Management Quality is 0.249 to the Consumer Loyalty variable, while it is also a multi-dimensional variable in this study, Management Quality is 0.900 to Product Quality Variables, 0.841 to Service Quality Variables, 0.897 to Design Quality Variables in the first stage.